REPORT OF THE 1961 PRESIDENT. - Carson, A. B. (The Accounting Review, 1962)
Abstract The American Accounting Association's follows dual objectives of fostering accounting research and improving accounting instruction. This article briefly summarizes each of the major activities that were carried on during the year 1961. The high quality of published articles was maintained in 1961. During the year more than 80 articles were published in addition to the professional examinations, association notes, and book reviews sections. The Membership Committee under leadership of Ralph F. Beckert had a very successful year. As a result of their efforts, over 1,000 new members were obtained. In 1961, seven education committees functioned under the general direction of Vice-President Norton M. Bedford, who also served as Chairman of the Joint Committee on Education. The Continuing Education Committee was asked to investigate the scope and nature of programs of formal study after a person has launched upon a career in accounting, and to inquire into the matter of suitable forms of instruction.